The movies as a world force : American silent cinema and the utopian imagination - Friedman, Ryan Jay (New Brunswick : Rutgers University Press, 2019)
The Movies as a World Force is the first analysis of utopian cinema writing; situating it in its proper intellectual contexts, theology, and political philosophy; and illustrating the ways in which its utopian imagination shapes and is shaped by the era's most prestigious film genre, the historical crowd epic.
Introduction: motion pictures and modern communion -- Enlightened public opinion: post-reform progressivism, mental science, and Gerald Stanley Lee's "moving-pictures" -- "The occult elements of motion and light": Vachel Lindsay's utopia of the mirror screen -- "The motion picture is war's greatest antidote": rescue as release of force in D.W. Griffith's Intolerance -- "Everything wooed everything": the triumph of morale over moralism in Rupert Hughes's Souls for sale -- "Little grains of sand": positive thinking and corporate form in Douglas Fairbanks's The thief of Bagdad -- Conclusion: universal history and the historicity of film entertainment.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Utopias in motion pictures; Silent films -- United States -- History; Utopies au cinéma.; Films muets -- États-Unis -- Histoire; PERFORMING ARTS -- General; Silent films; Utopias in motion pictures; United States; History